Finance and Development, December 2015. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2015)
This article presents an overview of the life of Richard Layard, who believes that the basic purpose of economics is the maximization of happiness and well-being. As director of the Wellbeing Programme at the London School of Economics' Centre for Economic Performance, Layard focuses on the study of happiness. Layard was a distinguished labor economist long before he turned his attention to happiness. He is best known for his research in the 1980s on unemployment and for his advocacy of policies to support unemployed people on the condition that they try to find work. This 'welfare to work' approach became popular in parts of continental Europe and was a mainstay of British Prime Minister Tony Blair's economic program. Layard's other current preoccupation is climate change. He is one of the drivers of the Global Apollo Program, a project to make renewable energy cheaper than fossil fuels within 10 years through publicly funded, internationally coordinated research and innovation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet